Asep Wirayasa (2022) CRISPR/CAS9 untuk Modifikasi Gen E7 pada HPV-6 dan HPV-11 sebagai Tatalaksana Kuratif Condyloma Acuminata - Asep Wirayasa (Jurnal Health Sains, 2022)
Sexually Transmitted Diseases (STDs) or Venereal Diseases (VD) are diseases that are transmitted through sexual intercourse, either vaginal, anal, or oral. HPV infection has a large number of about one million cases every day. One study conducted by WHO stated that 31% of women in Indonesia were exposed to infection from this virus. The HPV that can cause Condyloma Acuminata are HPV-6 and HPV-11. Although pharmacological and preventive therapies such as vaccines have been carried out, the number of sufferers is still increasing and becomes a burden for the country because in general this disease attacks the productive age population, so it is time to take a more sophisticated approach to the curative treatment of this disease. Looking for the latest curative methods that can stop condyloma acuminate permanently in each individual. The research method used is by conducting a literature study through several journal databases such as Pubmed, Cinahl, Google Scholar, and others. Based on several studies, it was found that CRISPR/Cas9 proved to be effective in suppressing the expression of the E7 protein and its sequence, proliferation and at the same time inducing apoptosis through the caspase-3 pathway in the conservative genome-specific proteins E7 HPV-6 and HPV-11. Not only decreasing expression and increasing deletion of the target genome, CRISPR/Cas9 has also been shown to be very efficient in suppressing cell proliferation. Keratin cells that have been exposed to the E7 HPV-6 and HPV-11 genomes will cause uncontrolled cell proliferation. With this method, the treatment of Condyloma Acuminata can be carried out effectively and efficiently so that it does not cause recurrence in the sufferer.